Out of Arabia: British Strategy and the Fate of Local Forces in Aden, South Yemen, and Oman, 1967–76. Issue 1 (1st January 2017) - Johnson, Rob
Abstract : The British engagement with Oman from 1967–76 came at a time when other imperial and defence commitments were being reduced in the Gulf region and elsewhere. Following the ignominious retreat from Aden, the British chose to support the Omani regime in its conflict with Communist-inspired insurgents (1970–6). This article gives context to the dichotomy of outcomes in southern Arabia and examines the role of local military forces in the counter-insurgencies. It demonstrates that Britain's domestic political considerations, regional strategic requirements, and concerns for its global reputation, rather than counterinsurgency operations and the local forces, were the main drivers of outcomes. Insurgents and local actors nevertheless responded to changes taking place in and around Oman, recalibrating their decision to co-operate or resist on their own terms, and changes in the international support for the insurgents were decisive. The key argument is that the dynamic combinations of international support, British strategic assumptions and miscalculations, and local agency, were crucially important to the outcomes in the region. The 'fate' of those who had allied with, or resisted, the British, needs to be set in this context.